2019
DOI: 10.1016/j.smr.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sport versus climate: Introducing the climate vulnerability of sport organizations framework

Abstract: Climate change presents a significant and growing challenge to the sport industry, especially outdoor and winter sports. The authors present a conceptual framework that elucidates the varying states of climate vulnerability a sport organization may face, so practitioners may better understand the risks of climate change. The authors developed the Climate Vulnerability of Sport Organizations (CVSO) framework by building on-and linking-concepts of climate vulnerability, exposure, sensitivity, and adaptive capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 84 publications
0
93
0
11
Order By: Relevance
“…High temperatures can also adversely affect people engaging in outdoor sports and recreation and represent a growing challenge for the sports industry (136). Heat is a leading cause of sudden death among athletes, and exertional heat illnesses cause thousands of debilitating health outcomes annually (18).…”
Section: Recreationmentioning
confidence: 99%
“…High temperatures can also adversely affect people engaging in outdoor sports and recreation and represent a growing challenge for the sports industry (136). Heat is a leading cause of sudden death among athletes, and exertional heat illnesses cause thousands of debilitating health outcomes annually (18).…”
Section: Recreationmentioning
confidence: 99%
“…Orr and Inoue [84] published a conceptual paper characterizing climate change vulnerability for sports organizations, by adapting the IPCC and United Nations International Strategy for Disaster Reduction guidelines to sport organizations. The authors suggested that sport organizations should anticipate the impacts of climate change on their equipment, finances, and the experiences of their athletes, staff, and spectators.…”
Section: Sport and Physical Activity Organizations Post-disastermentioning
confidence: 99%
“…They have done so through the lenses of sport sustainability Kellison & Hong, 2015;Mallen, Adams, Stevens, & Thompson, 2010), corporate social responsibility (Casper, Pfahl, & McSherry, 2012;Inoue & Kent, 2012a, 2012b, and sport industry's influence on proenvironmental behaviors (Casper, McCullough, & Pfahl, in press;Casper, Pfahl, & McCullough, 2017;Kellison & Kim, 2014;McCullough, 2013;Trail, 2016;Trail & McCullough, in press). Recently, a new line of research has emerged, exploring the impacts of climate change on the sport industry (Dingle & Stewart, 2018;Orr & Inoue, 2019) and adaptation behaviors of athletes, organizations, and fans (Orr & Schneider, 2018).…”
mentioning
confidence: 99%